Effect of six weeks forced and voluntary training before EAE induction on the expression of some adhesive molecules affecting the blood-brain barrier permeability - Mohammad Reza Rahmati; Mohammad Reza Kordi; Ali Asghar Ravasi (Shahid Beheshti University, 2022)
Purpose: Nearly 2.5 million people worldwide have multiple sclerosis, a chronic neuro-inflammatory disease of the brain and spinal cord that is a common cause of severe physical disability in young people, especially women. Therefore, the aim of this study was to investigate the effect of forced and voluntary training before EAE induction on the expression of adhesive molecule ​​(ICAM-1 and VCAM-1) affecting the blood-brain barrier permeability in C57BL/6 mice.Methods: Forty female C57BL/6 mice with weight 18 ± 2 g and age 7 ± 1 weeks were randomly divided to four groups of forced training (n = 12), voluntary training (n=12), EAE control (n = 8) and healthy control (n = 8). To perform the forced training, the mice performed swimming for 30 minutes five days/week for  six  weeks. Also to perform the voluntary training, the mice performed running wheel for one hour five days/week for six weeks. After that ICAM-1 and VCAM-1 gene expression were measured by RT-PCR. In data analysis, one-way ANOVA and Tukey's post-hoc test were applied to determine the difference between the groups.Results: Five weeks recording clinical signs after EAE induction showed a significant difference between the scores of the two training groups and EAE control (P < 0.05). Also, the expression of ICAM-1 and VCAM-1 adhesive molecules significantly decreased in the forced and voluntary groups compared to EAE control (P < 0.05), but the forced and voluntary groups significantly did not differ from the healthy control group (P > 0.05).Conclusion: The forced and voluntary training appears to reduce the blood-brain barrier permeability by reducing the expression of ICAM-1 and VCAM-1 adhesive molecules.